Genetic : Aplikasi Android Sebagai Media Promosi Musisi Indie - Setyadi, Heribertus Ary; Sutanto, Yusuf (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Promotion is important role in sustainability of a business, as well as creative business units such as music. Indie is one of music genres that is much loved by millennials, which is a movement of musicians who usually rarely follow market trends. Recording process to distribution is done independently. When active in the Indonesian music industry, many indie musicians experience difficulties due to the lack of promotion and distribution their music to general public. Many indie groups tend to use social media for promotion. See android applications or websites advantages that can be used as a forum for promotion and distribution of product information, in this study an android application was created as a media for indie group promos. System development method uses Rapid Application Development (RAD) because it involves users in designing and building a system. System can display information on indie bands along with copyrighted works in the form of songs and videos.
Keywords: Genetic; Promotion; Indie; RAD